Freedom of Association as a Pillar of The Democratic Rule of Law: A Normative Study of The ICCPR 1966 and Indonesian Law - Fatma Faisal; Syawal Amirul Syah (Candela Edutech Indonesia, 2026)
Freedom of association is a fundamental civil and political right that constitutes an essential component of a democratic state governed by the rule of law. This article examines the legal status of freedom of association within the framework of the International Covenant on Civil and Political Rights (ICCPR) 1966 and evaluates the extent to which Indonesian law complies with international human rights standards. The study employs normative legal research using statutory and conceptual approaches, supported by an analysis of relevant international human rights instruments and Indonesian constitutional and legislative provisions. The findings indicate that Article 22 of the ICCPR recognizes freedom of association as a fundamental right whose restriction is permissible only when it satisfies the cumulative requirements of legality, legitimate aim, necessity, and proportionality in a democratic society. Although Indonesia has constitutionally protected this right through Article 28E (3) of the 1945 Constitution and ratified the ICCPR through Law No. 12 of 2005, several regulatory and administrative practices continue to create inconsistencies with international standards. The originality of this study lies in developing an integrated normative framework that positions freedom of association not only as an individual human right but also as a constitutional principle supporting democratic governance under the rule of law. By systematically connecting Article 22 of the ICCPR with Indonesia's constitutional structure, this research offers a new analytical perspective on the harmonization of international human rights obligations and domestic constitutional law, while providing normative guidance for future legal reform aimed at strengthening democratic constitutionalism in Indonesia.